Pycnidiospore germination of Ascochyta rabiei, causal agent of chickpea blight, was significantly enhanced in low concentrations of malic acid (0.005 and 0.01%) but it was severely retarded at higher concentrations (1.5 and 2.0%). The total organic acids - and KOUSALYA GANGADHARAN, C. USHAMALINI, K. RAJAPPAN (Indian Phytopathology, 2002)
The effect of seed-borne fungi of cowpea (Macrophomina phaseolina, Fusarium oxysporum f.sp. tracheiphilum, Aspergillus flavus and A. niger), on the biochemical constituents (total sugars, reducing sugars, non-reducing sugars and protein) of stored seeds was studied. The maximum reduction in total sugars, reducing sugars and non-reducing sugars was recorded in seeds inoculated with F. oxysporum f.sp. tracheiphilum. After 30 days storage, the total sugar content of seeds inoculated with F. oxysporumf.sp. tracheiphilum, M. phaseolina, A. flavus and A. niger was 12.2, 12.4, 13.7 and 13.3 mg/g, respectively, compared with 16.2 mg/g in the control. The protein content was drastically reduced by M. phaseolina infection. The reduction in protein contentdue to F. oxysporum f.sp. tracheiphilum, A. niger and A. flavus infection was also significant. There was a negative correlation between storage period and sugar and protein content.